2019
DOI: 10.1002/cplu.201900405
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Benzene‐Based Fluorophore: Optical Waveguiding in the Crystal Form

Abstract: A single‐benzene‐based, blue‐emissive diethyl 2,5‐dihydroxyterephthalate (DDT) was prepared by Fischer esterification of 2,5‐dihydroxyterephthalic acid (DHT) and ethanol. The strong fluorescence in both the solution and the solid state from such a simple framework stemmed from the push‐pull structure of the electron‐donating hydroxy groups and the accepting carbonyl groups, as well as structural planarity from intramolecular hydrogen bonds. The strong intermolecular hydrogen bonds enabled DDT to crystallize ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…From the calculation of the intensity of main PL peaks, the average decay constant for the Alq 3 MCs was estimated to be 0.381 dB/µm. Considering that the propagated optical signal was measured, we suggested that they are a good candidate for potential materials for application in the development of optical communication devices [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…From the calculation of the intensity of main PL peaks, the average decay constant for the Alq 3 MCs was estimated to be 0.381 dB/µm. Considering that the propagated optical signal was measured, we suggested that they are a good candidate for potential materials for application in the development of optical communication devices [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A 100 mL two-neck round-bottom flask was charged with 2,5-dihydroxy-1,4-benzenedicarboxylic acid diethyl ester 68 (2.00 g, 7.86 mmol), EtOH (80 mL), and hydrazine hydrate (10 mL). The mixture was heated under reflux at 90 1C for 20 h, forming a large amount of a pale-yellow precipitate.…”
Section: Synthesis Of 25-dihydroxyterephthalohydrazide (Dhth)mentioning
confidence: 99%
“…One of the currently most active research directions in the field of adaptive organic crystals is exploring their potentials for application as optical waveguides for passive or active transduction of visible or near‐infrared light at the microscale. The optical waveguiding properties can be readily characterized for organic crystals that are centimeters to millimeters in length.…”
Section: Introductionmentioning
confidence: 99%
“…The optical waveguiding properties can be readily characterized for organic crystals that are centimeters to millimeters in length. It has been already demonstrated that owing to their high refractive indices (1.6–1.8) single‐component and hybrid organic crystals can be used as transducers of light. Some of these macroscopic crystal waveguides can be deformed—either mechanically, by applying force, or photochemically, by using ultraviolet light—to attain spatial control over their light output .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation